Assessment of structural characteristics of regenerated cellulolytic enzyme lignin based on a mild DMSO/[Emim]OAc dissolution system from triploid of Populus tomentosa Carr. Issue 6 (13th January 2017) - Chen, Tian-Ying; Wang, Bing; Shen, Xiao-Jun; Li, Han-Yin; Wu, Yu-Ying; Wen, Jia-Long; Liu, Qiu-Yun; Sun, Run-Cang
Abstract : The structural characteristics of native lignin are essential for the further deconstruction of plant cell walls for value-added application of lignocellulosic biomass. Abstract : The structural characteristics of native lignin are essential for the further deconstruction of plant cell walls for value-added application of lignocellulosic biomass. An improved protocol of cellulolytic enzyme lignin named regenerated cellulolytic enzyme lignin (RCEL) was developed in the present study. The dissolution process of poplar wood in the DMSO/[Emim]OAc dissolution system was dynamically monitored by microscopes and Confocal Raman Microscopy (CRM). The yield of RCEL (43.0–85.3%) was significantly higher than that of control CEL (30.6%). The isolated lignins were elaborately characterized by associated carbohydrates, 2D-HSQC NMR, 31 P-NMR, and GPC techniques. NMR results showed that RCELs had similar structural features as compared to CELs. The relative abundances of the major lignin linkages (β- O -4′, β–β′, β-5′, and β-1′) and linked molecules ( p -hydroxybenzoate) were quantitatively compared. Subsequent CP/MAS 13 C-NMR spectra of the regenerated substrates demonstrated that the structural changes of the cellulose in the substrates occurred during the dissolution and regeneration process, resulting in efficient enzymatic hydrolysis (63.2–88.7% vs. 49.5%), thus obtaining a high yield of extracted lignin (RCEL). In short, the understanding of native lignin in fast-growing poplar will contribute to the diversification of the biomass feedstock supply for designing effective deconstruction strategies for lignocellulosic biomass.